O Glide Path na Endodontia Contemporânea: Revisão de Literatura / The Glide Path in Contemporary Endodontics: Literature Review - Oliveira Martins, Danielle Fernandes; de Farias, Maria Clara Santos; Da Silva, Luiz Roberto Mendes (ID on line. Revista de psicologia, 2021)
Por meio deste estudo é possível analisar que a instrumentação dos canais radiculares após o uso do Glide Path traz inúmeros benefícios, incluindo o melhor deslizamento dos instrumentos, redução do número de fraturas e menor intercorrências intrarradiculares. Além disso, essa preparação inicial do canal radicular com o uso do Glide Path realiza uma desobstrução, criando um “caminho” livre para o melhor deslize dos instrumentos no canal radicular. Os instrumentos possuem características e particularidades que levam ao mesmo objetivo de preparar o conduto para uma segura instrumentação, destaca-se aqui o WaveOne Gold, R-Pilot e o PathFile. É uma técnica que vem sendo difundida e utilizada na endodontia contemporânea com o intuito de realizar um procedimento eficaz. — Abstract: Analyze the use of instruments to prepare the Glide Path and understand how this endodontic instrument brought advantages in instrumentation techniques. This is a literature review with selected articles from the last 10 years, in order to achieve the objectives proposed by the theme. Articles in English and Portuguese were used, with all information pertinent to the topic extracted. Through this study, it is possible to analyze that the instrumentation of root canals after the use of the Glide Path brings numerous benefits, including better sliding of the instruments, reduction in the number of fractures and less intra-radicular complications. In addition, this initial preparation of the root canal using the Glide Path performs clearance, creating a clear “path” for the best glide of the instruments in the root canal. The instruments have characteristics and particularities that lead to the same objective of preparing the conduit for safe instrumentation, the Wave One Gold, R-Pilot and PathFile stand out here. It is a technique that has been disseminated and used in contemporary endodontics with the aim of performing an effective procedure. Through this bibliographical study, it is possible to consider that the use of the Glide Path favors the preparation of the root canal and proves to be effective and safe when used before instrumentation, thus, with the creation of a more favorable environment for instrumentation, the chances of success in endodontic treatment.